Notch root strain measurement of WE43-T6 magnesium alloy using electronic speckle pattern interferometry - Liew H.L.; Ahmad A.; Ramesh S.; Purbolaksono J. (Elsevier Ltd, 2023)
The notch root elasto-plastic strains of circumferentially grooved round specimen of cast magnesium WE43-T6 were experimentally measured using the electronic speckle pattern interferometry (ESPI) and numerically evaluated using the finite element analysis (FEA). The specimens have notch radii of 1.6. mm and 0.8. mm and an opening angle of 60. The technique of ESPI showed its accuracy in measuring three-dimensional surface deformations on large negatively curved manifolds. The measured nominal stress for rupture is well beyond the ultimate strength, suggesting the existence of significant biaxial stress at the notch root region. The ESPI-based strains on the notch tips were shown to be in agreement with those evaluated by the FEA. The FEA also showed that the maximum elastic strain is shifted away from the notch root surface as the plastic strain is predominant. 2013 Elsevier Ltd.